AN ANALYSIS OF THE HUMAN DEVELOPMENT NEXUS IN ECONOMIC GROWTH DYNAMICS: REFRAMING AGEING AS OPPORTUNITY - Hu , Mingqi; Senawi, Azhan Rashid (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
Based on the panel data of 31 provincial administrative regions in China from 1990 to 2020, this paper employs the System GMM approach to study the impact of population aging on economic growth, as well as the mediating mechanism and moderating role of the Human Development Index (HDI). The results show that population aging significantly inhibits economic growth, which is consistent with existing international studies. At the same time, HDI can significantly promote economic growth and slow down the negative impact of population aging on economic growth. The intermediary effect test shows that part of the total effect of population aging on economic growth is indirectly realized through HDI, accounting for about 30% of the total impact, indicating that increasing HDI can partially offset the slowdown in growth caused by aging. The GMM estimation result of the system is robust, which has passed the correlation test of AR (1) and AR (2) sequences and the Hansen over-identification test, indicating that the model setting and the selection of instrumental variables are reasonable. The contribution of this paper is to reveal the significance of improving the level of human development in the context of population aging: on the one hand, it expands the theoretical understanding of the impact of population aging on economic growth, and emphasizes the intermediary mechanism of HDI, a comprehensive development indicator; On the other hand, it provides empirical evidence for formulating policies to actively respond to aging, and suggests that the level of human development should be comprehensively improved through education, health care and income distribution policies to alleviate the adverse impact of aging on the economy and achieve long-term sustainable growth.